Antimicrobial activities of silver nanoparticles bio-synthesized from diatom Amphora sp. - Tevan, Ramanathan; Govindaraju, M; Jayakumar, Saravanan; Govindan, Natanamurugaraj; Abd Rahim, Mohd Hasbi; Maniam, Gaanty Pragas; Ichwan, Solachuddin J. A. (RMP Publications, 2017)
A biological method was employed to synthesize silver nanoparticles through marine diatom Amphora sp. Antimicrobial efficacy test against different pathogenic bacteria were performed through synthesized silver nanoparticles. The physio-chemical properties of synthesized silver nanoparticles were studied using analytical techniques such as UV-Vis spectrophotometer, Field Emission Scanning Electron Microscopy (FESEM), Energy- Dispersive X-ray Spectroscopy (EDX) and Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Powder Diffraction (XRD). UV-Vis color intensity study and higher magnification of the Field Emission Scanning Electron Microscopy image showed the synthesized silver nanoparticles were rod shaped with a size range from 42 nm to 46 nm. The synthesized nanoparticles exhibited antibacterial activities in varying magnitudes. About 10 mg/ml of silver nanoparticles were able to inhibit the growth of gram-negative bacteria while gram-positive bacteria were resistant towards similar concentrations of silver nanoparticles.